2014
DOI: 10.5812/ircmj.13748
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis and Qualitative Study of Hemodialysis Patients, Family Experience and Perceived Social Support

Abstract: Background:Various treatments such as hemodialysis prolong the life of chronic renal failure disease patients who must tolerate many physical, emotional, social and economic difficulties. Therefore, social support is considered as a vital area of investigation for such patients.Objectives:In this qualitative research, a grounded theory approach was used and written as a content analysis form to study hemodialysis patients and family experience of perceived social support.Patients and Methods:Three nurses, 4 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Rosland et al (2010) also found that after marital partners, the most important sources of support for patients was their children, siblings, other family members, and friends (11). Other studies also confirmed this finding (7,23). Family members, especially spouses, play an important role in supporting the patients with chronic illnesses in their treatment regimen.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Rosland et al (2010) also found that after marital partners, the most important sources of support for patients was their children, siblings, other family members, and friends (11). Other studies also confirmed this finding (7,23). Family members, especially spouses, play an important role in supporting the patients with chronic illnesses in their treatment regimen.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that perceived social support significantly contributes to patients' physical and psychological well-being and their treatment (7)(8)(9). However, some other studies have shown that certain supportive behaviors do not contribute to patients' well-being, and instead can also damage it in some ways (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the evaluation process, two of these studies (Aghakhani et al . ; Grapsa et al . ) were deemed of low quality and were excluded from the review (see Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Two authors (AB and TG) independently reviewed the initial assessment and any discrepancies in assessment were resolved through discussion of the author team. As a result of the evaluation process, two of these studies (Aghakhani et al 2014;Grapsa et al 2014 deemed of low quality and were excluded from the review (see Supplementary Table S1).…”
Section: Inclusion and Evaluation Processmentioning
confidence: 99%
“…Naderaghakhni et. al., have referred about the patients who are handling the physical, emotional and economical barriers in their day to day life [57]. The frequency in dialysis destroys their ethical respect of the patient among their personal society and it also leads to increase in fear of dependency.…”
Section: International Journal Of Recent Technology and Engineering (mentioning
confidence: 99%